BURUH TANI WANITA PANGGILAN DAN EKSISTENSINYA MENURUT ADAT MINANGKABAU - helfi helfi (El Harakah, 2016)
Women farm call workers who are usually in groups are not common in Minangkabau, moreover who earn wages once a year. The more interesting one is that the wages they receive can be used as an alternative income by making it as a capital for other ‘bissiness’ in solving emergency problems at home. Minangkabau with its matrilineal system position woman respectfully which is usually called Bundokanduang. A proverb used is limpapeh rumah nan gadang, amban puruak pagangan kunci, sumarak dalam nagari. Discussion about women is a long non-finished discource yet. The high reward toward women in Minangkabau custom is not as beautiful as in the fact. The Minang ‘queens’ are let to compete freely on economic sector without seeing the gender.